The roots of cooperation - Zvonimir Bašić; Parampreet Christopher Bindra; Daniela Glätzle-Rützler; Angelo Romano; Matthias Sutter; Claudia Zoller (Max Planck Institute for Research on Collective Goods, 2024)
We study the developmental roots of cooperation in 929 young children, aged 3 to 6. In a unified experimental framework, we examine pre-registered hypotheses about which of three fundamental pillars of human cooperation - direct reciprocity, indirect reciprocity, and third-party punishment - emerges earliest and is more effective as a means to increase cooperation in a repeated prisoner's dilemma game. We find that already children aged 3 act in a conditionally cooperative way. Yet, direct and indirect reciprocity do not increase overall cooperation rates beyond a control condition. Compared to the latter, punishment more than doubles cooperation rates, making it the most effective mechanism to promote cooperation. We also find that children's cognitive skills and parents' socioeconomic background influence cooperation. We complement our experimental findings with a meta-analysis of studies on cooperation among adults and older children, confirming that punishment outperforms direct and indirect reciprocity.
hdl:21.11116/0000-000E-18FA-E
Keywords: C91; C93; D01; D91; H41; 330; Cooperation; reciprocity; third-party punishment; children; parents; prisoner's dilemma game; experiment; meta-analysis